Awareness on health programs in Kubza Village of Mokokchung District, Nagaland: A case study - *, Lendina; Naga, Moses M. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Health is one factor which everyone needs to take care of. Health programmes thatare launched by the Government needs to be made aware to all the rural people. This articlegives a survey report on awareness of some selected health programmes and the sources ofinformation used by the rural people to get information on health programmes. Awareness onhealth programmes was found to be very low. More awareness should be given to the ruralpeople on health programmes.